Eliminasi Non-Value Added Activity dengan Merancang Ulang Standard Operating Procedure: Studi Kasus di Sebuah Perusahaan Produksi Obat Nyamuk Bakar - Natasya Graciella Bernadine Boediono; I Nyoman Sutapa (Jurnal Titra, 2020)
This research has done at a manufacture company engaged in consumer good with many various product, one of there is mosquito coils. The mosquito coils have a variety of brand depending on concerned country. In the production process, often happen non-value added activity, especially on the production line number 5 which is used as a object of observation. This happen because the company doesn’t have standard operating procedure (SOP) for overall and work instruction (WI) for each process. This problem can be solved using SOP design for the overall production process and WI for each process that contained in the SOP. SOP and WI are re-designed with hope can help company in reducing the number of non-value added activities like rewrapping process, repacking process, and resealing master carton process. Reduction of non value added activity can help the companies to reduce waste from repetitive process like overproduction, overprocessing, inventory, motion, waiting, defects, and transportations.